2009
DOI: 10.5664/jcsm.27606
|View full text |Cite
|
Sign up to set email alerts
|

An Angry Bed Partner

Abstract: Figure 1-30-second epoch tracing of polysomnography recorded during REM sleep reveals persistent chin EMG tone during REM sleep, with overt whole-body movements at the end of the epoch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It has been estimated that the odds ratio of developing RBD is 1.9 with antidepressant use [ 27 ], particularly with selective serotonin reuptake inhibitors (SSRIs) and selective norepinephrine reuptake inhibitors (SNRIs). A few case reports have shown improvement of RBD upon discontinuation of fluoxetine [ 28 , 29 ], but RBD can persist for at least 19 months after discontinuation of SSRI medications [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that the odds ratio of developing RBD is 1.9 with antidepressant use [ 27 ], particularly with selective serotonin reuptake inhibitors (SSRIs) and selective norepinephrine reuptake inhibitors (SNRIs). A few case reports have shown improvement of RBD upon discontinuation of fluoxetine [ 28 , 29 ], but RBD can persist for at least 19 months after discontinuation of SSRI medications [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were also two unique features in this case. First, the latency to drug induced RBD was longer than the interval, usually less than 6 months, previously reported for SSRI induced RBD [ 10 , 14 ]. Actually, in our case, excessive EMG activity during REM sleep was found during the first PSG assessment taken when the patient had been taking duloxetine for 7 months, but without typical RBD symptoms.…”
Section: Discussionmentioning
confidence: 86%
“…In parallel, RSWA sharply decreased then almost completely disappeared after discontinuation of duloxetine for 9 and 37 days, respectively. Previous studies demonstrated that RBD symptoms remained after discontinuing fluoxetine for 6 weeks or even 27 months [ 14 , 15 ]. Similarly, RSWA persisted for a long time even though the abnormal behaviors had disappeared [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…When such intensification occurs in a negative context, it is nonetheless associated with improvements in symptoms of depression (60). Fluoxetine has also been incriminated in provoking episodes of RBD (61).…”
Section: Selective Serotonin Reuptake Inhibitor Antidepressantsmentioning
confidence: 99%